Identification of Slum Levels : Case Study of Tegal Besar Sub-District, Kaliwates District, Jember Regency) - Sukma Utami Rambe, Syavitri (Riviera Publishing, 2024)
Urban population growth in Indonesia is projected to increase by 2.75% annually, with 67% of the population expected to reside in urban areas by 2035. Rapid urban expansion without adequate basic services and infrastructure provision often leads to the formation of slum settlements. Slum settlements, as defined by Undang-Undang No. 1 of 2011, are areas deemed uninhabitable due to disorganized building layouts, high building density, and substandard infrastructure. Kaliwates District, identified as a regional activity center in Jember Regency's Spatial Plan (2013–2035), has the highest population density and growth rate in the regency, with a density of 5,140 people/km² and an annual growth rate of 106.06% from 2020–2023.One of the identified slum areas in the Kaliwates District is in RT02/RW01, Tegal Besar Sub-district, as designated in Jember Regent Decree No. 188.45/158/1.12/2024. This study uses quantitative and qualitative analysis through a descriptive approach to describe the characteristics of slum areas and analyze the level of slum areas by scoring. This study examines the existing conditions of the slum settlement in RT02/RW01. Evaluate its slum level based on seven variables and 19 criteria outlined in the Regulation of the Minister of Public Works and Housing No. 14/PRT/M/2018. The variables include building conditions, road infrastructure, drainage systems, wastewater management, solid waste management, and fire protection. The research result show that RT02/RW01, Tegal Besar Sub-district is categorized as medium slum areas.